Law Enforcement in Eradicating Corruption in Indonesia by Examining the Performance of Anti-Corruption Institutions and Obstacles in Realizing Clean Government - Rahmad Prasetyo; Suparno Suparno (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Corruption is a severe issue that threatens good government and impedes national growth. Various legislative tools, including Law Number 31 of 1999 in conjunction with Law Number 20 of 2001 concerning the Eradication of Criminal Acts of Corruption, have been used in Indonesia to combat corruption, as well as the establishment of special institutions such as the Corruption Eradication Commission (KPK). Although regulations and institutions for eradicating corruption are available, the implementation of the law in the field still faces various obstacles, including weak coordination between law enforcers, political intervention, and the effectiveness of sanctions imposed on perpetrators of corruption. The study seeks to analyze the legal framework governing corruption eradication in Indonesia and identify obstacles in its implementation. This study also looks at legal tactics that can be used to improve the efficacy of anti-corruption efforts. This study takes a normative legal approach and concentrates on analyzing pertinent laws and regulations, court records, and scholarly works. This study's data came from secondary sources including books, scientific journals, and reports from anti-corruption organizations, as well as primary sources like relevant laws and regulations. It is anticipated that this investigation will provide a deeper insight of the effectiveness of the law in eradicating corruption in Indonesia and to find aspects that need to be improved in the existing legal system. Thus, this study can provide academic contributions and practical recommendations for policymakers to strengthen the eradication of corruption in Indonesia. In addition to analyzing the legal framework and challenges, this study also explores the role of public awareness and participation in the fight against corruption in Indonesia. Public involvement, such as through the reporting of corrupt activities and participation in anti-corruption campaigns, can significantly contribute to strengthening anti-corruption efforts.